Umbilical Cord Coiling in High-risk Pregnancies: Associations With Determinants of Adverse Birth Outcomes and Iron Status. (November 2018) - Steinl, Gabrielle K; Gandelman, Jocelyn S; Katzman, Philip J; Ru, Yuan; Guillet, Ronnie; Pressman, Eva; Cooper, Elizabeth M; O'Brien, Kimberly O
Abnormal umbilical cord coiling has been associated with adverse neonatal outcomes, but the etiology of these findings remains poorly characterized. This study was undertaken to examine associations between cord coiling and maternal iron (Fe) status and to identify potential determinants of hypo- and hypercoiling in 2 higher risk obstetric groups: pregnant adolescents (≤18 years, n = 92) and adult women carrying twins (n = 49), triplets (n = 11), or quadruplets (n = 1). Umbilical cords were classified as hypo-, normo-, or hypercoiled using digital photographs to assess gross appearance. Hypocoiling and hypercoiling were observed in 44% (n = 86/195) and 13% (n = 26/195) of the combined study population. The prevalence of hypocoiling among women carrying multiples was over 3-fold higher than the prevalence in singleton pregnancies based on the published data. Within the entire study population, hypocoiling was associated with a lower gestational age at birth when compared to normocoiling and hypercoiling (36.3 ± 3.6 weeks [n = 86] vs 37.8 ± 2.7 [n = 83], P  < .01, and 38.2 ± 2.6 [n = 26], P  < .01, respectively), whereas hypercoiling was associated with significantly lower serum ferritin when compared to normocoiling ( P  < .01) and hypocoiling ( P  < .001). In the multiples cohort only, hypercoiling was significantly associated with multiparity ( P  < .01) and lower birth weight ( P  < .05). Further studies are needed to identify the determinants and consequences of cord coiling.